2012
DOI: 10.1136/bmj.e497
|View full text |Cite
|
Sign up to set email alerts
|

Drugs for relief of pain in patients with sciatica: systematic review and meta-analysis

Abstract: Objective To investigate the efficacy and tolerability of analgesic and adjuvant pain drugs typically administered in primary care for the management of patients with sciatica. Design Systematic review.Data source International Pharmaceutical Abstracts, PsycINFO, Medline, Embase, Cochrane Central Register of Clinical Trials (CENTRAL), CINAHL, and LILACS.Study selection Randomised controlled trials assessing the efficacy and tolerability of drugs versus placebo or other treatment for sciatica. Data extractionTw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
142
2
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(163 citation statements)
references
References 52 publications
3
142
2
5
Order By: Relevance
“…Our findings differ from previous evidence on anticonvulsants for lumbar radicular pain, in which a 2012 BMJ review reported a treatment benefit of gabapentin based on a single trial. 15 One key reason for the difference in our review is the inclusion of a 2017 study that found pregabalin was no more effective than placebo in patients with sciatica. 30 Clinically, the prescription of anticonvulsants for back and neck pain, including radicular pain in primary care, has increased by 535% in the last 10 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings differ from previous evidence on anticonvulsants for lumbar radicular pain, in which a 2012 BMJ review reported a treatment benefit of gabapentin based on a single trial. 15 One key reason for the difference in our review is the inclusion of a 2017 study that found pregabalin was no more effective than placebo in patients with sciatica. 30 Clinically, the prescription of anticonvulsants for back and neck pain, including radicular pain in primary care, has increased by 535% in the last 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reviews were limited only to populations with chronic back pain, 14 and new evidence may affect conflicting and limited conclusions. 5,15 Therefore, this systematic review aimed to determine the efficacy and tolerability of anticonvulsants in the treatment of low back pain and lumbar radicular pain compared with placebo.…”
Section: Methodsmentioning
confidence: 99%
“…In cases in which wrist ROM was reported only as a percentage of the contralateral (normal) wrist, we converted percentages to a degree measurement based on normal physiologic ROM (normal values used: 85°flexion, 80°ex-tension, 85°supination, 80°pronation, 35°ulnar deviation, and 20°radial deviation) [7,28]. Means and standard deviations (SDs) were collected when reported; medians were used in place of means when the latter was not reported because these provide an acceptable alternate measurement for centrality [35]. Where data were reported only in graph format, GraphClick software [14] was used to extract the relevant values.…”
Section: Study Selection and Data Extractionmentioning
confidence: 99%
“…Sciatica is traditionally diagnosed within patients presenting with primary complaints of unrelenting sharp pain, which travels profusely down the leg. Cases of mild to moderate sciatica are witnessed but at a much rarer occurrence, with patients presenting with mild to moderate pain and paresthesias [1][2][3][4][5][6][7][8][9][10]. Ordinary patients may present with or without neurological deficits such as numbness and weakness of the leg and/ or foot, in more severe cases patients may present with foot weakness causing difficulty and/or inability to ambulate.…”
mentioning
confidence: 99%